ROLES OF WOMEN AFFECTING THE DEVELOPMENT OF SUBDISTRICT MUNICIPALITIES IN NAKHON RATCHASIMA PROVINCE - Sirisorawongse , Nichabha (Journal of MCU Nakhondhat, 2023)
The research purposes were 1) to study the development levels of subdistrict municipalities in Nakhon Ratchasima Province; 2) to analyze the roles of women affecting the development of subdistrict municipalities in Nakhon Ratchasima Province; and 3) to present the guidelines for development of subdistrict municipalities in Nakhon Ratchasima Province. This was the quantitative and qualitative research. The quantitative sample group was the 400 people, the research instrument was the questionnaire; the qualitative key informants consisted of 22 people, the research instrument was the in - depth interview form. The data analysis statistics were the frequency, percentage, mean, standard deviation, and multiple regression analysis. The research findings were 1) the development of subdistrict municipalities in Nakhon Ratchasima Province found the overall was at high level ( = 3.59, S.D. = 0.19), the descending mean were the social aspect ( = 3.66, S.D. = 0.27), the political aspect ( = 3.61, S.D. = 0.32), and the economic aspect ( = 3.50, S.D. = 0.31), respectively; 2) the analysis of the women’ roles that affected the development of subdistrict municipalities in Nakhon Ratchasima Province, the women’ roles on the economic aspect and the women roles on the administration aspect affected the development of subdistrict municipalities in Nakhon Ratchasima Province at statistical significant level .05 but women’s roles in other aspects had none of statistical significance level; and 3) the suggestion of the approach for subdistrict development in Nakhon Ratchasima Province should support the development of women's potential to become well - rounded in both the administration aspect and the economic aspect, give an opportunity for women’ roles in social activities, as well as encouraging women to be more involved in social roles to keep up with the changing environment and the model to drive women's role in sustainable community development.